MENGOPTIMALKAN POTENSI PUSTAKAWAN DALAM MENUNJANG TRI DHARMA PERGURUAN TINGGI - Triningsih Triningsih (Jurnal Pustaka Ilmiah, 2016)
This paper discusses the optimization of potential librarians in supporting Tri DharmaPerguruan Tinggi. The purpose of this paper is to explain how optimizations canbe made by librarians in supporting the goals of college education. This potentialoptimization can be realized with the role optimization that librarians can perform.These roles include the role of leader, educator, administrator, supervisor, motivator,and true friend. This needs to be done because librarians are the spirit of the library,so the optimization of the role must be realized by the Librarian in order to achievethe goal of the college library that is functioning to support the implementation of TriDharma Higher Education from the college that shelter it.